Islamic Rhetoric Analysis on Congregational Emotions in Ustadzah Halimah Alaydrus’ Lecture on YouTube - Samsudin, Saskia Verellita; N, Nasichah; Ahsan, Muin Nur (Madani: Jurnal Ilmiah Multidisiplin, 2026)
In the era of digital da'wah, social media platforms such as YouTube have become new spaces for preachers to deliver religious messages. One example is the lecture by Ustadzah Halimah Alaydrus titled “Don’t Be Sad, Prophet Muhammad Loves You”, presented through simple animation without directly showing the preacher. This study aims to analyze the influence of Islamic rhetoric on the emotions of the congregation in the lecture. The method used is descriptive qualitative through video observation and content analysis of language style, narrative, and audience responses in the comment section. The analysis is conducted using Aristotle’s rhetorical theory (ethos, pathos, logos) and the theory of religious emotions. The results indicate that the aspects of pathos and ethos are the most dominant, through the use of gentle language, stories of the Prophet’s exemplary character, and reassuring messages. These strategies successfully evoke positive emotions such as being touched, calmness, and love for the Prophet. Thus, Islamic rhetoric plays a role in strengthening the emotional and spiritual closeness of the congregation in the context of digital da'wah.